Molecular Confirmation of Taenia crassiceps Cysticercosis in a Captive Ring-Tailed Lemur (Lemur catta) in Poland - Małgorzata Samorek-Pieróg; Jacek Karamon; Adam Brzana; Lesław Sobieraj; Mariusz Włodarczyk; Jacek Sroka; Aneta Bełcik; Weronika Korpysa-Dzirba; Tomasz Cencek (Pathogens, 2022)
(1) Background: Taenia crassiceps is a cosmopolitan tapeworm endemic to the northern hemisphere with an indirect lifecycle. Its definitive hosts are carnivores, and its intermediate hosts are rodents and rabbits. Nonhuman primates in zoos appear to be highly susceptible to T. crassiceps cysticercosis. The aim of this study was to confirm the presence and the molecular characterization of T. crassiceps cysts isolated from a captive ring-tailed lemur. (2) Methods: Surgery revealed multifocal, transparent saccules containing several thin-walled tapeworm cysticerci. In some of the metacestodes, single or multiple exogenous buds from daughter cysticerci were spotted. A molecular analysis was performed to confirm our morphological examinations, using two protocols to obtain the partial nad1 and cox1 genes of the Taenia sp. (3) Results: On the basis of morphological features and molecular analysis, the cysticerci were identified as T. crassiceps metacestodes, and products taken from the PCRs were sequenced. With respect to interpreting the sequencing results of the obtained amplicons, we compared them with data in the GenBank database, proving that, in this case, the causative agent was indeed T. crassiceps. (4) Conclusions: The received data can be used to supplement descriptions of this species. To the best of our knowledge, this is the first case of cysticercosis caused by T. crassiceps in a nonhuman primate in Poland.